STRATEGI DAN TEKNIK PENULISAN ARTIKEL ILMIAH MENUJU JURNAL TERAKREDITASI SINTA 1 - Samsuri, Samsuri; Hayadi, B.Herawan; Saputra, Dicky Wahyu; Fitriani, Pina; Tresna, Popy Wulandari; Ningsih, Devi Sri Cahya (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
Scientific publication in Sinta 1 accredited journals poses a significant challenge for academics due to rigorous standards and high rejection rates. This article aims to describe comprehensive strategies and technical managerial techniques for scientific writing to successfully navigate top-tier journals. Using a literature review approach and empirical analysis, this study explores five main pillars of publication success: constructing titles with global appeal, strengthening State of the Art (SOTA) through gap analysis, digitalizing reference management based on Reference Manager Software, paraphrasing techniques for plagiarism mitigation, and navigating the editorial system through the Open Journal System (OJS). The results indicate that publication success is determined not only by the depth of research data but also by the author’s ability to communicate novelty and meet technical managerial compliance. This article provides a practical contribution as a systematic guide for researchers and academics in improving the quality of national publications toward international standards.